Synthesis method of interlocking functionalized metal organic framework and application of interlocking functionalized metal organic framework to adsorption of Th (IV)

By preparing DBT-BZTA-Zn material with a dual interpenetrating structure, the problem of difficulty in removing Th(IV) in a strong acidic environment is solved, and the Th(IV) adsorption effect is achieved with high efficiency and strong selectivity, and excellent performance in acid-base stability and cyclic stability are shown.

CN119591888APending Publication Date: 2025-03-11NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411676430.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove the associated radioactive element thorium (Th(IV)) in rare earth tailings wastewater in a highly acidic environment, and the chemical stability and long-lasting adsorption properties of the materials are insufficient.

Method used

Using 4,4'-bis(4H-1,2,4-triazole-4-yl)-1,1'-biphenyl (DBT) and 1,2,4,5-benzene tetracarboxylic acid (BZTA) as biligands, an interlocking functionalized metal organic framework (DBT-BZTA-Zn) with a dual interpenetrating structure was prepared. The material has high crystallinity and acid-base stability in the pH range of 1-13.

Benefits of technology

DBT-BZTA-Zn material exhibits excellent chemical stability and efficient adsorption performance under strong acid conditions. Its selective adsorption capacity for Th(IV) is significantly improved, with a maximum adsorption capacity of 548 mg/g, and maintains good removal efficiency in multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591888A_ABST
    Figure CN119591888A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method of an interlocking functionalized metal organic framework and application of the interlocking functionalized metal organic framework to adsorption of Th (IV), and belongs to the technical field of environmental protection. An interlocking functional metal organic framework material is prepared, a special double interpenetrating structure endows the interlocking functional metal organic framework material with high stability, due to interpenetrating, non-coordinated carboxyl in a three-dimensional channel of the interlocking functional metal organic framework material and a triazole nitrogen group jointly form an N and O synergistic interlocking cavity nano trap structure, and the shape and the size of pore cavities are matched with those of Th (IV). In addition, the electronegativity of the framework is enhanced by unsaturated carboxylic acid sites in the interlocking cavity, and transmission of Th (IV) in the three-dimensional pore channel is accelerated. The metal organic framework prepared by the method has excellent adsorption performance on Th (IV), can selectively remove Th (IV), and has good application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental protection, and in particular relates to a synthesis method of an interlocking functionalized metal organic framework and its adsorption application to Th(IV). Background Art

[0002] With the rapid development of the rare earth industry, the mining process of rare earth mines is usually accompanied by the production of a large number of associated radioactive elements, which will inevitably be released into the environment. The long half-life, strong radioactivity and strong chemical toxicity of the associated radioactive element thorium (Th(IV)) not only affect the purification effect of rare earths, but also cause harm to the environment (Maes, S., Zhuang, W.-Q., Rabaey, K., Alvarez-Cohen, L., Hennebel, T. ConcomitantLeaching and Electrochemical Extraction of Rare Earth Elements from Monazite. Environmental Science&Technology, 2017, 51(3), 1654-1661). Th(IV) can also be used as an important nuclear energy resource and converted into clean energy that is beneficial to mankind. Exploring efficient thorium removal materials and separation technologies is not only conducive to the purification of rare earths, but also can effectively alleviate energy problems and reduce environmental pollution. Therefore, separating Th(IV) from rare earths and comprehensively utilizing other valuable elements and minimizing radioactive waste in minerals can realize the resource utilization of Th(IV), which is beneficial to the sustainable use of rare metal resources and environmental protection, and is in line with the concept of green and sustainable development.

[0003] Th(IV) separation and recovery technologies include membrane filtration, ion exchange, chemical / electroprecipitation, photocatalysis and adsorption separation, among which adsorption separation has the advantages of simple operation and low cost, and has become one of the most promising methods for separation and recovery of Th(IV). Various adsorbents including carbon materials (biochar, graphene and carbon nanotubes), metal oxides (TiO2, Al2O3 and MgO), minerals (fly ash, kaolin and diatomaceous earth), framework materials (metal organic frameworks and covalent organic frameworks) and organic materials (chitosan, starch and xanthan gum) have been used to separate Th(IV) (Liao, J., Xiong, T., Zhao, Z., Ding, L., Zhu, W., & Zhang, Y. Synthesis of a Novel Environmental-friendly Biocarbon Composite and its Highly Efficient Removal of Uranium(VI) andThorium(IV) from Aqueous Solution. Journal of Cleaner Production, 2022, 374, 134059).

[0004] Metal-organic frameworks (MOFs) are framework materials with porous network structures constructed by inorganic metal nodes and organic ligands. MOFs have high specific surface area and porosity, and are widely used in multifunctional adsorption and monitoring enrichment (storage, separation, catalysis, detection, biomedical imaging and drug delivery, etc.). These characteristics make MOFs an ideal material for extracting radionuclides (Zhang, N., Yuan, L.-Y., Guo, W.-L., Luo, S.-Z., Chai, Z.-F.,Shi, W.-Q. Extending the Use of Highly Porous and Functionalized MOFs to Th(IV) Capture. ACS Applied Materials&Interfaces, 2017, 9(30), 25216-25224). The adsorption efficiency of porous adsorption materials is easily affected by material morphology, active sites modified by functional groups, etc. In addition, rare earth tailings wastewater is usually highly acidic, which poses a huge challenge to the construction of highly stable materials to remove the associated radioactive Th(IV) elements. It is necessary to introduce strong coordination bonds, stable skeletons and acid-resistant functional groups to ensure the structural integrity and long-lasting adsorption performance of the materials (Song, A.-M., Yang, M.-J., Wu, Z., Yang, Q., Lin, B., Liang, R.-P., Qiu, J.-D. Rational Designed Metal-Organic Framework with Nanocavity Traps forSelectively Recognizing and Separating of Radioactive Thorium in Rare Earth Wastewater. Advanced Functional Materials, 2024, 2406932).Long flexible ligands and highly electronegative multidentate carboxylic acid ligands help to construct interpenetrating structures and form stable, easily modifiable small pores, thereby increasing the number of binding sites for Th(IV) and facilitating the efficient removal of Th(IV) in strong acid environments (Hu, Q.-H., Song, A.-M., Gao, X., Shi, Y.-Z., Jiang, W., Liang, R.-P., Qiu, J.-D. Rationally Designed Nanotrap Structures for Efficient Separation of Rare Earth Elements Over a Single Step. Nature Communications, 2024, 15(1), 1558). Therefore, the interpenetrating strategy is expected to construct multifunctional adsorbent materials with acid-base stability, which is of great significance for the study of Th(IV) adsorption. Summary of the invention

[0005] The purpose of the present invention is to provide a method for synthesizing an interlocking functionalized metal organic framework and its application in the adsorption of Th(IV). In the present invention, 4,4'-di(4H-1,2,4-triazole-4-yl)-1,1'-biphenyl (DBT) and 1,2,4,5-benzenetetracarboxylic acid (BZTA) are used as dual ligands to react with metal-centered zinc ions to prepare an interlocking functionalized metal organic framework material (DBT-BZTA-Zn) with excellent acid-base stability and high crystallinity in the pH range of 1-13. The three-dimensional cavity of DBT-BZTA-Zn contains abundant unsaturated carboxyl sites, which form three-dimensional N,O functionalized interlocking cavity nanotraps (3.5 Å) under the action of the triazole nitrogen group in the building unit DBT in a two-fold interpenetrating conformation. These cavities are more adaptable to the size and shape of Th(IV) and can serve as binding sites for Th(IV). The abundant carbonyl oxygen atoms in the three-dimensional cavity of DBT-BZTA-Zn can enhance the negative charge of the framework and accelerate the mass transfer of Th(IV), thus enhancing the selective adsorption performance of DBT-BZTA-Zn for Th(IV). Theoretical calculation simulations were further used to reveal the mechanism of action between DBT-BZTA-Zn and Th(IV). DBT-BZTA-Zn was used to achieve the selective and efficient removal of Th(IV) in the strongly acidic tailings waste leachate, which has good application potential.

[0006] The present invention provides a method for synthesizing an interlocking functionalized metal organic framework, comprising: Take 4,4'-di(4H-1,2,4-triazole-4-yl)-1,1'-biphenyl and 1,2,4,5-benzenetetracarboxylic acid as raw materials, add zinc precursor and solvent and mix evenly, raise the temperature to 130-150 ℃ and react at constant temperature, cool after the reaction to obtain colorless transparent crystals, and then wash by vacuum filtration to obtain a three-dimensional porous interlocking functionalized zinc-based metal organic framework.

[0007] Furthermore, the zinc precursor is Zn(NO3)2·6H2O.

[0008] Furthermore, the molar ratio of the 4,4'-di(4H-1,2,4-triazol-4-yl)-1,1'-biphenyl, 1,2,4,5-benzenetetracarboxylic acid, and the zinc precursor is 1:1:(1.1-1.4).

[0009] Furthermore, the isothermal reaction time is 72 h; the programmed temperature rise is 6 h to 140 ° C; and the cooling is 24 h to room temperature.

[0010] Furthermore, the solvent is composed of a mixture of acetonitrile and water, and the volume ratio of acetonitrile to water is 2:8.

[0011] The present invention also provides the use of the interlocking functionalized metal organic framework obtained by the synthesis method in the adsorption of Th (IV).

[0012] Furthermore, the interlocking functionalized metal organic framework can selectively adsorb Th(IV) under the condition of pH=1-5 and the coexistence of multiple interfering ions; the multiple interfering ions include UO2 2+ Sc 3+ , Y 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ Mg 2+ 、Al 3+ , Ca 2+ Cr 6+ , Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2 +, K + 、Na + .

[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The interlocking functionalized metal organic framework prepared by the method of the present invention has a double interpenetrating structure, which gives it excellent chemical stability and is conducive to the efficient adsorption of Th(IV) under strong acidic conditions.

[0014] 2. The present invention reveals the interaction mechanism between the interlocking functionalized metal organic framework and Th(IV) by combining experiments with theoretical calculation simulations.

[0015] 3. The interlocking functionalized metal-organic framework prepared by the method of the present invention belongs to the triclinic system. The uncoordinated carboxyl groups and triazole nitrogen groups in its cavity form N,O functionalized interlocking cavity nanotrap structures under the action of two-fold interpenetrating conformation, which is more adaptable to the size and shape of Th(IV) and can serve as the binding site of Th(IV).

[0016] 4. The interlocking functionalized metal organic framework prepared by the method of the present invention contains abundant carbonyl oxygen atoms, which can enhance the electronegativity of the framework and accelerate the mass transfer of Th(IV), thereby enhancing the selective adsorption performance of Th(IV).

[0017] 5. Compared with traditional adsorbents, the interlocking functionalized metal organic framework prepared by the method of the present invention can be used for the removal of Th(IV) in strongly acidic tailings waste leachate, and has the advantages of good selectivity, high removal efficiency and large adsorption capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The single crystal structure of DBT-BZTA-Zn: (a) Metal center Zn 2+ Coordination environment; (b) Two-dimensional structure of DBT-BZTA-Zn on the ac plane observed along the b-axis; (c) Double interpenetrating framework structure of DBT-BZTA-Zn, green and blue represent two interpenetrating layers, respectively; (d) Nanopocket with a diameter of 3.5 Å formed by the triazole ring of DBT-BZTA-Zn and the uncoordinated carboxylic acid groups in the channel.

[0019] Figure 2 Experimental and simulated PXRD patterns of DBT-BZTA-Zn.

[0020] Figure 3 Experimental and simulated PXRD patterns of DBT-BZTA-Zn under different pH conditions.

[0021] Figure 4 FT-IR graphs of DBT-BZTA-Zn under different pH conditions.

[0022] Figure 5 This is the adsorption isotherm of DBT-BZTA-Zn for different concentrations of Th(IV).

[0023] Figure 6 This is the removal selectivity diagram of DBT-BZTA-Zn for Th(IV).

[0024] Figure 7 This is the adsorption cycle stability diagram of DBT-BZTA-Zn for Th(IV). DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0027] Example 1: Synthesis and Characterization of DBT-BZTA-Zn 0.100 mmol of 4,4'-di(4H-1,2,4-triazol-4-yl)-1,1'-biphenyl (DBT), 0.100 mmol of 1,2,4,5-benzenetetracarboxylic acid (BZTA), 0.125 mmol of Zn(NO3)2·6H2O, 2 mL of acetonitrile (CH3CN) and 8 mL of H2O were mixed evenly, and the mixed solution was placed in a 25 mL reactor, and the temperature was programmed to 140 ℃ within 6 h, and the reaction was kept at 140 ℃ for 72 h. After the reaction was completed, the temperature was programmed to room temperature within 24 h. The obtained colorless crystalline solid was vacuum filtered, washed with ethanol and water, and dried to obtain a three-dimensional porous interlocking functionalized metal-organic framework crystal material (DBT-BZTA-Zn).

[0028] Figure 1 The single crystal structure of DBT-BZTA-Zn is shown in Figure 2. The crystal structure of DBT-BZTA-Zn was measured using an X-ray single crystal diffractometer. DBT-BZTA-Zn is a three-dimensional porous zinc metal organic framework. Figure 1 (a) It can be seen that the metal center Zn 2+ In orthogonal space groups P It coordinates with the triazole N atoms on two DBT molecules and the carboxyl O atoms on four BZTA molecules. Figure 1 (b) It can be seen that along the b-axis, DBT-BZTA-Zn presents a cross-porous structure on the ac plane. The large number of carbonyl functional groups distributed in the pores enhance the negative charge of the framework, which is conducive to the efficient mass transfer of metal ions. Figure 1 (c) and (d) show that due to the special double interpenetrating structural characteristics, DBT-BZTA-Zn contains a large number of N,O functionalized interlocking cavity nanotrap structures (3.5 Å) modified by uncoordinated carboxyl groups and triazole nitrogen groups in DBT. These cavities are more adapted to the size and shape of Th(IV) and can serve as binding sites for Th(IV).

[0029] Figure 2 The experimental and simulated single crystal X-ray diffraction (PXRD) patterns of DBT-BZTA-Zn are shown in Figure 1. By comparing the theoretical PXRD derived from single crystal data and the PXRD spectra of DBT-BZTA-Zn crystal powder collected experimentally, it is found that the PXRD pattern of DBT-BZTA-Zn powder collected experimentally has obvious diffraction peaks at 2θ angles of 10.81°, 11.29°, 18.03° and 22.87°, which match the characteristic peaks of the theoretical PXRD spectrum derived from single crystal data, indicating that DBT-BZTA-Zn with high crystallinity is synthesized by the method of the present invention.

[0030] Figure 3 The experimental and simulated PXRD patterns of DBT-BZTA-Zn under different pH conditions. By comparing the theoretical PXRD derived from single crystal data and the PXRD spectra of DBT-BZTA-Zn crystal powder collected experimentally under different pH conditions, it is found that the PXRD spectra of DBT-BZTA-Zn powder collected in the pH range of 1-13 all have obvious diffraction peaks, and match the characteristic peaks of the simulated PXRD spectra, indicating that the DBT-BZTA-Zn synthesized by the method of the present invention has excellent acid-base stability.

[0031] Figure 4 The Fourier transform infrared spectra (FT-IR) of DBT-BZTA-Zn under different pH conditions. Figure 4 It can be seen that after being immersed in aqueous solutions with pH values ​​of 1, 3, 5, 7, 9, 11, and 13 for 12 h, the FT-IR spectrum of DBT-BZTA-Zn remains almost unchanged, indicating that the DBT-BZTA-Zn synthesized by the method of the present invention has good chemical stability. The above results show that DBT-BZTA-Zn has excellent stability and has the potential to remove Th(IV) in strongly acidic tailings waste leachate.

[0032] Example 2: Adsorption of Th(IV) by DBT-BZTA-Zn (1) Adsorption capacity of DBT-BZTA-Zn for Th(IV) At pH 3, 50 mg of DBT-BZTA-Zn was added to 50 mL of a solution containing different concentrations of Th(IV) (0-1000 ppm). The suspension was stirred for 2 h and filtered through a 0.22 μm microporous membrane. The concentration of Th(IV) in the filtrate was measured by inductively coupled plasma mass spectrometry (ICP-MS), and the adsorption capacity of DBT-BZTA-Zn for Th(IV) was calculated. Figure 5 is the adsorption isotherm of DBT-BZTA-Zn for different concentrations of Th(IV). Figure 5 It can be seen that due to the presence of a large number of N,O functionalized interlocking cavity nanotrap structures and a large number of uncoordinated carbonyl-modified three-dimensional porous channels, the adsorption capacity of DBT-BZTA-Zn for Th(IV) increases with the increase of Th(IV) concentration until the adsorption equilibrium is reached. The maximum adsorption capacity of DBT-BZTA-Zn for Th(IV) is 548 mg / g, which is higher than most traditional adsorbents. e / q e With C e There is a good linear relationship, which is consistent with the Langmuir adsorption model, indicating that the adsorption of Th(IV) by DBT-BZTA-Zn is a monolayer chemical adsorption.

[0033] (2) Removal of Th(IV) from samples by DBT-BZTA-Zn At pH 3, 50 mg of DBT-BZTA-Zn was added to 50 mL of tailings waste leachate containing Th(IV). The suspension was stirred for 2 h and filtered through a 0.22 μm microporous filter membrane. The concentrations of Th(IV) and coexisting ions in the filtrate were measured by ICP-MS, and the removal rate of Th(IV) and coexisting ions by DBT-BZTA-Zn was calculated. Figure 6 The removal selectivity of DBT-BZTA-Zn for Th(IV) is shown in Figure 2. Figure 6 It can be seen that DBT-BZTA-Zn has the best removal effect on Th(IV), while it has the best removal effect on other coexisting ions (UO2 2 + Sc 3+ , Y 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ Mg 2+ 、Al 3 + , Ca 2+ Cr 6+ , Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , K + 、Na + ) had almost no removal effect, indicating that DBT-BZTA-Zn had good adsorption selectivity for Th(IV).

[0034] Figure 7 The adsorption cycle stability diagram of DBT-BZTA-Zn for Th(IV) is shown in Figure 2. Figure 7 It can be seen that the adsorption performance of DBT-BZTA-Zn for Th(IV) has good removal efficiency and elution efficiency in at least seven adsorption / desorption cycles, indicating that DBT-BZTA-Zn has excellent cyclic stability and the adsorption process of Th(IV) is reversible.

[0035] The breakthrough test results of DBT-BZTA-Zn on Th(IV) in acidic tailings waste leachate show that compared with transition metal ions, rare earth ions and actinide ions, DBT-BZTA-Zn has a higher adsorption capacity and a larger breakthrough bed volume for Th(IV), with the breakthrough volume reaching 426 bed volumes. 2+ Sc 3+ , Y 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3 + 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ Mg 2+ 、Al 3+ , Ca 2+ Cr 6+, Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , K + 、Na + The above results show that DBT-BZTA-Zn can be used as a material for the efficient extraction of Th(IV) from strongly acidic tailings waste leachate.

[0036] The first-principles calculations of the N,O functionalized interlocked cavity nanotrap building blocks in DBT-BZTA-Zn for representative ions (Th(IV), Nd 3+ 、Al 3+ 、UO2 2+ ) is adsorbed. If the adsorption energy ( E ads ) is less than zero, indicating that spontaneous interaction can occur between the material and the ions; the more negative the adsorption energy, the stronger the binding between DBT-BZTA-Zn and the ions. The adsorption energy of DBT-BZTA-Zn for Th(IV) is -543.49 kJ / mol, indicating that the binding of the N,O functionalized interlocking cavity nanotrap structural unit in DBT-BZTA-Zn with Th(IV) is a spontaneous process, which can be attributed to the existence of a nanotrap binding mechanism between DBT-BZTA-Zn and Th(IV). The adsorption energy of other ions by the N,O functionalized interlocking cavity nanotrap structural unit in DBT-BZTA-Zn was calculated. The adsorption energy of Th(IV) ( E ads Th = -543.49.7 kJ / mol) is much larger than other ions ( E ads Nd = -381.14 kJ / mol, E ads Al = -96.21 kJ / mol, E ads U = -60.41 kJ / mol), and the absolute values ​​of the adsorption energy are in the order of Th(IV)>Nd(III)>Al(III)>U(VI), which further indicates that DBT-BZTA-Zn has excellent adsorption selectivity for Th(IV).

[0037] It can be seen that the DBT-BZTA-Zn prepared by the method of the present invention has good adsorption and removal performance for Th(IV), and can be used for efficient and selective adsorption and removal of Th(IV) in strongly acidic tailings waste leaching solution.

[0038] The embodiments described above only express several preferred embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but are not intended to limit the present invention. It should be noted that for those skilled in the art, the present invention may also have various changes and modifications, and any modifications, equivalent substitutions, improvements, etc. made within the concept and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for synthesizing an interlocking functionalized metal organic framework, characterized in that: include: Take 4,4'-di(4H-1,2,4-triazole-4-yl)-1,1'-biphenyl and 1,2,4,5-benzenetetracarboxylic acid as raw materials, add zinc precursor and solvent and mix evenly, raise the temperature to 130-150 ℃ and react at constant temperature, cool after the reaction to obtain colorless transparent crystals, and then wash by vacuum filtration to obtain a three-dimensional porous interlocking functionalized zinc-based metal organic framework.

2. A method for synthesizing an interlocking functionalized metal organic framework according to claim 1, characterized in that: The zinc precursor is Zn(NO3)2·6H2O.

3. A method for synthesizing an interlocking functionalized metal organic framework according to claim 1, characterized in that: The molar ratio of the 4,4'-di(4H-1,2,4-triazole-4-yl)-1,1'-biphenyl, 1,2,4,5-benzenetetracarboxylic acid and the zinc precursor is 1:1:(1.1-1.4).

4. The method for synthesizing an interlocking functionalized metal organic framework according to claim 1, characterized in that: The isothermal reaction time is 72 h; the temperature is raised to 140° C. in 6 h; and the cooling is lowered to room temperature in 24 h.

5. The method for synthesizing an interlocking functionalized metal organic framework according to claim 1, characterized in that: The solvent is composed of a mixture of acetonitrile and water, and the volume ratio of acetonitrile to water is 2:

8.

6. Use of the interlocking functionalized metal organic framework obtained by the synthesis method according to any one of claims 1 to 5 in the adsorption of Th(IV).

7. The use according to claim 6, characterized in that: The interlocking functionalized metal organic framework can selectively adsorb Th(IV) at pH = 1-5 and under the condition of coexistence of multiple interfering ions; the multiple interfering ions include UO2 2+ Sc 3+ , Y 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ Mg 2+ 、Al 3+ , Ca 2+ Cr 6 + , Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , K + 、Na + .